Common and distinct neural networks involved in fMRI studies investigating morality: an ALE meta-analysis. (4th July 2018) - Eres, Robert; Louis, Winnifred R.; Molenberghs, Pascal
ABSTRACT: Morality is an important social construct necessary for understanding what is right and wrong. Neuroimaging studies investigating morality have used a wide variety of paradigms and implicated many different brain areas. Yet, it remains unclear whether differences amongst morality tasks are the cause for such heterogeneous findings. Therefore, in the present study, a series of activation likelihood estimation (ALE) meta-analyses were conducted on 123 datasets (inclusive of 1963 participants) to address this question. The ALE meta-analyses revealed a series of common brain areas associated with all moral tasks, including medial prefrontal cortex, lateral orbitofrontal cortex, amygdala, temporoparietal junction, and precuneus. However, individual and contrast analyses also revealed unique networks associated with each moral modality, suggesting that different moral tasks recruit specialised brain regions.